Dialektika Pernikahan Anak Perspektif Fiqh dan Undang Undang No. 1 Tahun 1974 - Arifin, M Nasrul (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The institution of marriage is God's grace in order to maintain the dignity, dignity and dignity of human beings in order to ensure the continuity of human regeneration as a caliph on earth, and in Islamic studies, that a marriage that is the shari'a of God, then in its implementation must be in accordance with the provisions of Islamic teachings, namely it must be in accordance with the terms of marriage, and in the context of social life of the community, the state is present to ensure public order and order social, therefore a law was drafted that discussed marriage, and in the context of Indonesia, there is Law No. 1 of 1974. The existence of marriage rules in the review of shari'i, following the drafting of the Marriage Law, naturally there are differences in some rules that often cause controversy in the midst of social life, for example in the case of early marriage, therefore in this research, we will explore what exactly is the terminology of marriage and early marriage. This research also questions the law of early marriage from the perspective of Islamic fiqh, and also questions the results of the dialectic of al-Islam fiqh and law. No. 1 of 1974 as rules that are present in the midst of the Indonesian Muslim community.This study is a literature research using content analysis techniques to get answers from several references relevant to the title of this study, either references classified from primary sources or from secondary sources